Insulin‐like growth factor‐1 secreted by brain microvascular endothelial cells attenuates neuron injury upon ischemia. (18th June 2013) - Wang, Jun; Tang, Yibo; Zhang, Wei; Zhao, Haiping; Wang, Runjun; Yan, Yangyang; Xu, Liwei; Li, Pengtao
<x xml:space="preserve">Abstract</x> Insulin‐like growth factor (IGF)‐1 is essential for the development of the nervous system, and is present in many cell types. Relatively little is known about IGF‐1 expression in brain microvascular endothelial cells (BMECs). For in vivo studies, we examined the expression of IGF‐1 and insulin‐like growth factor‐binding protein (IGFBP)‐2 after focal cerebral ischemia for 12 h, 24 h, 3 days and 7 days, utilizing a permanent middle cerebral artery occlusion (MCAO) model in rats. For in vitro studies, we examined the levels of IGF‐1 and IGFBP‐2 in the culture medium or primary culture of BMECs injured by oxygen–glucose deprivation (OGD). Then, we elucidated the protective effects of IGF‐1 on cortical neurons injured by OGD and the possible mechanism. In addition, we investigated the effect of BMEC‐conditioned medium on IGF‐1 receptor expression in neurons. The results showed that IGF‐1 expression increased in serum and brain tissue, whereas IGFBP‐2 expression decreased in brain tissue of MCAO‐injured rats. In primary culture of BMECs, the expression levels of IGF‐1 and IGFBP‐2 were significantly higher under OGD conditions in culture. IGF‐1 administration improved neuron viability upon normoxia or OGD, and upregulated p‐Akt expression. This effect was reversed by LY294002, a specific inhibitor of the phosphoinositide 3‐kinase–Akt signaling pathway. Furthermore, conditioned medium from OGD‐treated BMECs substantially suppressed neuron viability and the expression of IGF‐1 receptor simultaneously. These data demonstrate that therapeutic strategies that prioritize the early recovery of the IGF‐1 system in BMECs might be promising in ischemic injury.